Marknadsetablering i Indien - Nilsson, Gustav; Olsson, Philip (2009)
The demand from Swedish companies of new potential markets to enter is increasing. One of these companies is Väderstad-verken which has the vision to grow approximately 15 percentages every year. To make this possible they must find new emerging markets to enter to be able to grow.